Diaphragm plication by thoracoscopy by two ports in diaphragmatic paralysis - Gutiérrez-Puente Edgard (Revista Ciencias Biomédicas, 2013)
Introduction: Diaphragmatic paralysis is produced by interruption in the transmissionof nerve impulses by means of the phrenic nerve or by loss of the muscle contractility.It entails to progressive muscular atrophy and to distension of the cupola. It can appearunilaterally or bilaterally, being this one the most common; however, it is a condition oflow incidence. The causes are tumour invasion of the phrenic nerve, surgical, traumaticand idiopathic lesions and infections, between others. Its surgical correction is necessarywhen respiratory commitment exists. Several techniques and approaches are describedto do repair. Publications about diaphragmatic plication by thoracoscopy by two portsare unknown.Clinical case: It is presented a clinical case of a 50 years old female patient withidiopathic diaphragmatic paralysis, progressive dyspnea with suggestive spirometrydata of severe restrictive pattern. Diaphragmatic plication by thoracoscopic way bytwo ports was carried out satisfactorily. Anatomical and clinical improvements wereconfirmed.Conclusion: Diaphragmatic plication is the surgical technique of choice to repairdiaphragmatic paralysis. The videothoracoscopy by two ports is proposed as a favorableapproach that allows the development of the surgical procedure. Rev.cienc.biomed.2013;4(1):142-146.RESUMENIntroducción: la parálisis diafragmática se produce por interrupción en la transmisiónde los impulsos nerviosos a través del nervio frénico o por pérdida de la contractilidaddel músculo. Conlleva a atrofia muscular progresiva y distensión de la cúpula. Puedepresentarse bilateral o unilateralmente, siendo esta última más común; sin embargo,es una afección de baja incidencia. Las causas son invasión tumoral del nervio frénico,lesiones quirúrgicas, traumáticas, infecciones, idiopáticas, entre otras. Su correcciónquirúrgica es necesaria cuando hay compromiso respiratorio. Varias técnicas y abordajesestán descritos para realizar reparación. No se conocen publicaciones de plicaturasdiagramáticas realizadas por videotoracoscopia por dos puertos.Caso clínico: se presenta caso clínico de paciente femenina de 50 años de edad conparálisis diafragmática idiopática. Disnea progresiva, con datos espirométricos sugestivosde patrón restrictivo severo. Se realizó satisfactoriamente y sin complicaciones plicaturadiafragmática vía toracoscópica por dos puertos. Se comprobó mejoría anatómica yclínica.Conclusión: la plicatura diafragmática es la técnica quirúrgica de elección parala corrección de la parálisis diafragmática. Se propone la videotoracoscopia por dospuertos como abordaje favorable que permite realización del procedimiento operatorio.Rev.cienc.biomed.2013;4(1):142-146